2006
DOI: 10.1146/annurev.nucl.56.080805.140456
|View full text |Cite
|
Sign up to set email alerts
|

CP Violation and the CKM Matrix

Abstract: Our knowledge of quark-flavor physics and CP violation increased tremendously over the past five years. It is confirmed that the Standard Model correctly describes the dominant parts of the observed CP -violating and flavorchanging phenomena. Not only does CP violation provide some of the most precise constraints on the flavor sector, but several measurements performed at the B-factories achieved much better precision than had been expected. We review the present status of the Cabibbo-Kobayashi-Maskawa matrix … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 177 publications
3
70
0
Order By: Relevance
“…A measurement of the double ratio involving B u → τ ν, D → µν, D s → µν/τ ν and B s → µ + µ − would enable a complementary measurement of the CKM matrix element V ub [5,7,8] with a theoretical error which is much smaller than that present in the conventional approaches to measure |V ub | (which utilize inclusive and exclusive semi-leptonic decays of B mesons). We quantified the experimental error in a possible future measurement of |V ub | using the above double ratio, and showed that it can be competitive with the anticipated precision from the conventional approaches.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A measurement of the double ratio involving B u → τ ν, D → µν, D s → µν/τ ν and B s → µ + µ − would enable a complementary measurement of the CKM matrix element V ub [5,7,8] with a theoretical error which is much smaller than that present in the conventional approaches to measure |V ub | (which utilize inclusive and exclusive semi-leptonic decays of B mesons). We quantified the experimental error in a possible future measurement of |V ub | using the above double ratio, and showed that it can be competitive with the anticipated precision from the conventional approaches.…”
Section: Discussionmentioning
confidence: 99%
“…A complementary technique for which the theoretical error is known to be small is particularly attractive. In this regard, the use of double ratios of leptonic decays to measure |V ub | was proposed in [5,7,8]. One such double ratio is defined by:…”
Section: The Double Ratiomentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, study of decays of heavy flavor mesons, especially the B mesons, has played an important role (see refs. [7][8][9][10] for some recent reviews). In our analysis we shall exploit the isospin symmetry, which is known to be a very useful symmetry in the study of various hadronic decays, most notably in many B meson…”
Section: Introductionmentioning
confidence: 99%